Peran SDM Kompetitif dalam Meningkatkan Kualitas Pelayanan dan Produktivitas pada Anugerah Digital Printing Maumere - Maria Silvana Mariabel Carcia; Ferlina Pora; Maria Ayuni Nona Melci; Maria Benedikta Jawa Liwun; Maria Alusia Inpona (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
Printing businesses such as Anugerah Digital Printing Maumere face increasingly fierce competition, yet many have not fully implemented the concept of competitive human resources effectively. This study aims to analyze the role of competitive human resources in improving service quality and work productivity. The method used involves direct interviews with management and literature studies. The results indicate that the current condition of human resources still faces several challenges, including a lack of mastery of new technology, limited creativity and innovation, and a need for improved discipline. The efforts undertaken to address these issues include skills training and development, provision of motivation and rewards, optimization of technology usage, and establishment of a positive work culture. The implementation of these strategies has proven effective in enhancing employee performance and service quality. This research provides practical implications for business owners in their efforts to increase company competitiveness despite limited resources..